ANALlSIS ENERGI DAN SEBARAN SUHU PADA GASIFIER UNGGUN TETAP - Yogi Sirodz Gaos; Armansyah H. Tambunan; Kamaruddin Abdullah; Prawoto Prawoto (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT Performance test of Imbert Downdraft Gesifier by using cyclone as an auxiliary for tar filtering has been conducted with three kinds of feeding chips, i. e; borneo wood, tamarind wood and leucena wood. The research has been developed to support as an energy source for combined heat power generation. Gesifier will be coupled to diesel generating set and waste heat from the exhaust gas will be used as energy source for an adsorption type refrigeration system. The test had produced the best combustible gas with the chemical composition CO = 55,59 %, CH4 = 0,14 %, C2H6 = 0,3 % and C3H8= 0, 08 %. The maximum temperature 1142 oC has been found in oxidation zone based on the leucena wood test, meanwhile the calculation result of energy availability for the combustible gas was 60,39 kW and specific energy availability was 0,082 kg/kWh. The test result of temperature distribution along the reactor compare to numerical solution of mathemathicai modelling has got the similar curve. Diterima: 26 Pebruari 2007, Disetujui: 25 Mei 2007